Dr. Ibrahim Temo - The Founder of the Young Turks Committee “Unity and Progress” - Kaleši, Hasan (Prilozi za orijentalnu filologiju, 2017)
(The contribution to the clarification of the role of the Albanians in the Young Turks Revolution) Dr. Ibrahim Temo, the founder of the Young Turks Committee “Unity and Progress” is not unknown either in Turkish or Albanian historiography. But in both of them his role has been presented rather one-sidedly. In Turkish historical works, as well as in the foreign ones published in Europe, which deal with the young Turks Movement, Temo has been mentioned only as the founder of this Committee; a few details about his arrest and escape to Romania, and his founding of the Democratic Party of Turkey have been given, but his cultural and educational activity among the Turks of Dobrudja has not been mentioned; nothing is known about his works written in Turkish nor about his various activities concerning the Albanian National Movement. On the other hand, Dr. I. Temo is mentioned in the Albanian historical works, but his. cultural and educational activity, his works, even his activity as a publisher have also remained, completely unknown. However, Temo's role both as a fighter against the sultan's absolutism, and as fighter for the political, cultural and educational emancipation of the Albanian people, is much greater and far more complex. In this article, an attempt is made for the first time to present a more complete biography of Ibrahim Temo, and to clarify some important and, at the same time, unknown moments from his life and work. numerous aspects of his political, cultural, educational activities have been clarified on the basis of his autobiography published in Medjidiye, Romania, in 1939, data which the author of this article has obtained in Constanza from his son, Dr. Naim Terno, and on the basis of the files and various material from Temo's library. His activities among the Turks of Dobrudja are also mentioned for the first time, and his works, of which some have been published in Turkey and some in Romania, are also listed for the first time. Already in 1898, he began contributing to Albanian newspaper and magazines; this fact has been totally unknown up .to now. During the Balkan War Temo was the chief of a Romanian Red Cross Mission in Istanbul, and during the Prince Wiede's rule he was the chief of the same Mission in Albania. In 1913, after his return from Albania, he founded a printing firm called “Işik” (The Lightening) in Turkish, and began publishing the weekly magazine called “Işik” which be edited himself, and for which he wrote and translated most of the material. As a member of the Albanian Settlement in Romania he took part in the Peace Conference held in Paris. After World War I, I. Temo was elected senator in the Romanian Parliament, and owing to his permanent struggle and great authority he contr1buted to the opening of the Turkish schools for the Turkish minority in Romania, and to their cultural .and educational development. Also discussed is Temo’s participation in the Albanian National Movement, and a number of the previously unknown cases are given. In addition, the biographies of many of Temo's collaborators are reconstructed in brief. Most of them were Albanians like Temo himself. The numerous errors appearing in many works about Temo, published so far, are also corrected. Through Temo's case the author wanted to emphasize particularly the role of certain Albanians, coming from the Yugoslav territory, who played an important role in the recent Turkish and Albanian history, and whose role is minimized in the contemporary Albanian historiography only because they come from our country.